Aplikasi Pengingat Minum Obat Dengan Monitoring Tenaga Kesehatan Berbasis Mobile Menggunakan Metode Prototype - Firdaus Al Anwari, M Riadi; Nuraeni, Fitri; Cahyana, Rinda; Fitriani, Leni; Setiawan, Ridwan; Septiana, Yosep (Institut Teknologi Garut, 2025)
The process of administering medication to patients requires timeliness and consistency to ensure optimal therapeutic outcomes. In practice, many patients struggle to remember their medication schedules, particularly when treatment extends over a long period. Addressing this issue, the present study aims to develop an Android-based medication reminder application that assists patients in adhering to their treatment schedules while enabling healthcare providers to digitally monitor patient activity. The application was designed using a prototyping method, which emphasizes iterative system development based on user feedback. The development process was conducted in two phases. The first phase involved initial design and testing of core features, such as reminder notifications and patient medication intake reporting forms. The second phase focused on improvements based on user feedback, particularly the addition of a disease information feature that provides educational content about patient diagnoses following checkups, such as hypertension and tuberculosis. Testing was carried out using a black-box testing approach to ensure proper functionality, alongside feedback collection through interviews. The results showed that the application performed effectively; its features were usable by both patients and healthcare providers as intended, and the information displayed was considered helpful in enhancing patients’ understanding of their health conditions. Furthermore, the system contributed to improving patient adherence to medication regimens and facilitated continuous monitoring by healthcare providers.